Development of a novel alginate‐polyvinyl alcohol‐hydroxyapatite hydrogel for 3D bioprinting bone tissue engineered scaffolds. Issue 5 (25th February 2017) - Bendtsen, Stephanie T.; Quinnell, Sean P.; Wei, Mei
Abstract: Three‐dimensional printed biomaterials used as personalized tissue substitutes have the ability to promote and enhance regeneration in areas of defected tissue. The challenge with 3D printing for bone tissue engineering remains the selection of a material with optimal rheological properties for printing in addition to biocompatibility and capacity for uniform cell incorporation. Hydrogel biomaterials may provide sufficient printability to allow cell encapsulation and bioprinting of scaffolds with uniform cell distribution. In this study, a novel alginate‐polyvinyl alcohol (PVA)‐hydroxyapatite (HA) hydrogel formulation with optimal rheological properties for 3D bioprinting of mouse calvaria 3T3‐E1 (MC3T3) cells into scaffolds of high shape fidelity has been developed. A systematic investigation was conducted to determine the effect of varying concentrations of alginate, phosphate, calcium, and the PVA‐HA suspension in the formulation on the resulting viscosity and thus printability of the hydrogel. HA, the main mineral component in natural bone, was incorporated into the hydrogel formulation to create a favorable bone‐forming environment due to its excellent osteoconductivity. Degradation studies in α‐MEM cell culture media showed that the 3D printed alginate‐PVA‐HA scaffolds remained in‐tact for 14 days. MC3T3 cells were well distributed and encapsulated throughout the optimal hydrogel formulation and expressed high viability through the completion of the 3D printing process. Thus, the development of this novel, osteoconductive, biodegradable, alginate‐PVA‐HA formulation and its ability to 3D bioprint tissue engineered scaffolds make it a promising candidate for treating personalized bone defects. © 2017 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 105A: 1457–1468, 2017.